2018
DOI: 10.15171/ijoem.2018.1159
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Effects of Exposure to Gasoline Fumes on Petrol Pump Workers

Abstract: Background: Petrol pump workers are occupationally exposed to gasoline and its fumes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
(29 reference statements)
2
12
0
5
Order By: Relevance
“…exposed to formaldehyde. 32,36 The present findings observed in buccal cells also typified the cytotoxic effects of cement dust.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…exposed to formaldehyde. 32,36 The present findings observed in buccal cells also typified the cytotoxic effects of cement dust.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, Shaikh, et al, has reported similar effects caused by exposure to gasoline among petrol pump workers. 32 Nuclear changes, other than MN, that represent cellular death, which can enhance the sensitivity of techniques to detect genotoxicity, have been reported by many researchers. [33][34][35] The factors intimately involved in cell growth and death are affected by toxic agents; an increased cell proliferation indicates carcinogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…В последние годы для прогнозирования риска развития рака у лиц, связанных с влиянием на организм длительно существующих вредных привычек (курение, алкогольная зависимость), с действием факторов внешней среды, про-фессионального вреда широко используется цитогенетическая характеристика ядер соматических немалигнизированных клеток -образование МЯ вследствие повреждения ДНК, гибель клеток, пикноз, кариолиз и кариорексис [25][26][27][28][29][30][31][32].…”
Section: цитогенетические цитотоксические эффекты и изменения молекуunclassified
“…Apart from the skin, and respiratory lesions, a high risk of cancer caused by benzene, cytotoxicity and genotoxicity affecting the integrity of DNA in petrol station workers have been reported [33][34][35][36][37]. The consequences of petrol on the health of vendors vary depending on the length of exposure and become more dangerous for those who have spent several years in this business [38].…”
Section: Health Related Consequences Due To Exposure To Petrolmentioning
confidence: 99%